Observation of a water-depletion region surrounding loblolly pine roots by magnetic resonance imaging. - MacFall, J S (1990)
Magnetic resonance imaging was used to study sand containing various amounts of water and roots of loblolly pine planted into similar sand. Spin-lattice (T1) relaxation times of sand with water contents ranging from 0 to 25% (wt/wt) ranged from 472 to 1265 ms and increased with water content. Spin-spin (T2) relaxation times ranged from 54 to 76 ms and did not change in a discernible pattern with water content. Based on water content and measured T1 and T2 values, the signal intensity of sand/water images was predicted to increase with water content in a linear fashion, with the slope of the lines increasing with the time of acquisition repetition (TR). Measured signal intensity from images of sand with various water contents was found to follow a similar pattern. This allows interpretation of dark images of sand/water to be regions of low water content, and bright images to have comparatively greater water content. Images of loblolly pine seedling roots planted in identical sand showed the formation of a distinct water-depletion region first around the woody taproot and later showed the region extended and expanded around the lateral roots and clusters of mycorrhizal short roots. This observation strongly suggests that water uptake is occurring through the suberized region of the woody taproot.